Hubungan Akses Ke Posyandu, Dukungan Keluarga, Dan KeluhanFisik Dengan Keaktifan Lansia Mengikuti Kegiatan PosyanduPuspasari Abadi V Di Gonilan Kartasura - Hidawati, Lathifah; , Abi Muchlisin, S.KM., M.Kep (2016)
Quality of life in old age will be maintained properly and optimally if Posyandu activities can be run well and makes it easy for the elderly to get basic health care. A wide variety of programs and activities of Posyandu is very good and provides many benefits for the elderly. In order for the health of the elderly can be maintained and monitored well, then the elderly can seek to utilize their best of the Posyandu. But the reality on the ground shows a different fact, that IHC Elderly was only crowded in the early establishment only, furthermore seniors who utilize Posyandu diminishing. This study aims to determine the relationship of access to neighborhood health center, family support, and physical complaints with the liveliness of the elderly in following the activities of elderly Posyandu "Eternal Puspasari V" in the village of Gonilan Kartosuro. This research is non experimental quantitative research with descriptive analytic method is by using cross sectional study design. The population in this study were all elderly Posyandu Elderly "Eternal Puspasari V" in the village of Gonilan, District Kartosuro totaling 53 people. The sample used in this study were enrolled in the entire elderly Posyandu Elderly "Eternal Puspasari V" in the village Gonilan, District Kartosuro totaling 53 techniques used in sampling is total sampling. Data analysis techniques used by menggunakanan univariate, bivariate and multivariate analyzes. Based on the results of the study showed no significant effect on the activity of access to Posyandu elderly in participating in Posyandu activities shown by the significant value of Chi-Square 0.069> 0.05. there is the influence of family support for the elderly activeness in participating in Posyandu activities shown by Chi-Square 0.049 <0.05 and there is a significant effect on the activity of the elderly physical complaints elderly in participating in Posyandu activities showed with Chi-Square 0026 <0 05. Judging from the results of ANOVA showed physical complaints is a dominant factor influencing the activity of the elderly. Keywords : Access to neighborhood health center, Family support, Liveliness, Physical complaints.